Analysis of the Relationship between Consumer Ethnocentrism and Cultural Values of Consumers - Štefko, Róbert; Rigelský, Martin; Ondrijová, Ivana (Technium Business and Management, 2024)
This paper examines the relationship between consumer ethnocentrism and cultural values using two primary analytical tools: the CETSCALE and the Portrait Value Questionnaire (PVQ). The primary aim of this research is to elucidate how individual cultural values influence ethnocentric attitudes towards domestic and foreign products. The study addresses a significant gap in understanding the nuanced interactions between cultural orientations and consumer behavior. Systematization of existing literature and methodologies reveals that consumer ethnocentrism can be influenced by various cultural values. Investigation begins with a correlation analysis to explore the universal relationships among different PVQ indicators and their association with CETSCALE scores. Following this, an ordinal logistic regression analysis was employed to assess the impact of individual PVQ values on CETSCALE outcomes. Methodological tools included Spearman’s rank correlation and ordinal logistic regression, applied to data from a sample of 288 respondents collected between January 26, 2024, and March 2, 2024. The analysis highlighted significant positive correlations, particularly between the values of Tradition and Security and ethnocentric attitudes, with Tradition showing the most substantial impact. The paper’s findings underscore that while certain values, specifically Tradition and Security, significantly affect ethnocentric tendencies, the overall influence of PVQ scores on CETSCALE is relatively modest. This modest effect is further supported by low R² values, indicating that while statistically significant, the practical impact of cultural values on ethnocentrism is limited. The relevance of addressing this scientific problem lies in the need for a deeper understanding of how cultural values shape consumer preferences and behaviors. The empirical results confirm and theoretically substantiate that Tradition and Security are key predictors of ethnocentric attitudes. These insights can be valuable for policymakers, marketers, and businesses aiming to navigate consumer preferences in a multicultural context and develop strategies that align with cultural values.